Kedai Kek Shah Alam / Muhammad Ghazali Kasim ... [et al.] - Kasim, Muhammad Ghazali; Juhari, Muhammad Ikmal; Jailani, Muizzuddin; Rahman, Nurul Liyana; Kamaruzaman, Kamalina Azyyati (2019)
Kedai Kek Shah Alam is a bakery located in the Ole-Ole Mall at Seksyen 18. The bakery sells variety of product line such as cakes and pastries. The bakery came out with the concept of low cost cake where they sells all their cakes with the affordable price as lowest as RM 20 for the whole cake. They also accepted some vendor or local entrepreneur and provided some space for them to sell their products. The cakes were produced at their factory at Cheras, Kuala Lumpur and then were sold at the bakery.